Structure, biological activities and synthesis of hyacinthacine alkaloids and their stereoisomers - Ritthiwigrom T. (2014)
This review reports on recent developments on the structure, biological activities and synthesis of hyacinthacine alkaloids and related compounds. © 2012 Bentham Science Publishers.